PERBEDAAN KINERJA KEUANGAN SEBELUM DENGAN SESUDAH AKUISISI TERHADAP PERUSAHAAN YANG TERDAFTAR DI BEI - Sinta Rahayu; Diah Lestari Mumpuni (MANAJEMEN DEWANTARA, 2018)
Â The purpose of this study was to know (1) the difference Operating Profit Margin before with after acquisition (2) the difference Earning Per Share before with after acquisition, and (3) the Debt to Equity Ratio before with after acquisition.This Study classified as a quantitative research. The population is a company listed on the Indonesia Stock Exchange (IDX), do acquisitions in 2013. The samples were companies listed on the Stock Exchange during the study and the companies that make acquisitions in 2013 with years of observations from 2011 to 2015, the date the acquisition is clear, available reports Detailed financial five quarterly before and after each company. Methods of data collection using the method of documentation, while data analysis techniques using testing T (T-test).The results showed that the Operating Profit Margin, Earnings Per Share before and after the acquisition was not a significant. The different results obtained in Debt to Equity Ratio before to after the acquisition there are significant differences.Keywords: Operating Profit Margin, Earning Per Share, Debt to equity Ratio, acquisition.